Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under him: Alexander Berkman and G.P. Maksimov
Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under him: Alexander Berkman and G.P. Maksimov.